2018
DOI: 10.1038/s41467-018-06972-x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical shifts in molecular solids by machine learning

Abstract: Due to their strong dependence on local atonic environments, NMR chemical shifts are among the most powerful tools for strucutre elucidation of powdered solids or amorphous materials. Unfortunately, using them for structure determination depends on the ability to calculate them, which  comes at the cost of high accuracy first-principles calculations. Machine learning has recently emerged as a way to overcome the need for quantum chemical calculations, but for chemical shifts in solids it is hindered by the che… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
305
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 216 publications
(323 citation statements)
references
References 72 publications
9
305
0
Order By: Relevance
“…Finally, an application of ML models that has received far less attention in other reviews is their potential to enhance experimental characterization. The interpretation and labeling of experimental images (e.g., scanning transmission electron microscopy (STEM)) and spectra (e.g., X‐ray diffraction (XRD), X‐ray absorption near‐edge structure (XANES), nuclear magnetic resonance (NMR), etc.) are today still mostly painstakingly carried out by humans.…”
Section: Applicationmentioning
confidence: 99%
“…Finally, an application of ML models that has received far less attention in other reviews is their potential to enhance experimental characterization. The interpretation and labeling of experimental images (e.g., scanning transmission electron microscopy (STEM)) and spectra (e.g., X‐ray diffraction (XRD), X‐ray absorption near‐edge structure (XANES), nuclear magnetic resonance (NMR), etc.) are today still mostly painstakingly carried out by humans.…”
Section: Applicationmentioning
confidence: 99%
“…In a system with relatively uniform atom density, the overlap between environments X j |X k is dominated by the region farthest from the center. This could be regarded as rather unphysical, since interactions between atoms decay with distance and the closest atoms should therefore give the most significant contribution to properties, which is reflected in the observation that multi-scale kernels tend to perform best when very low weights are assigned to the long-range kernels 3,57,65 . This effect can be counteracted by multiplying the atomic probability amplitude Eq.…”
Section: B Radially-scaled Kernelsmentioning
confidence: 99%
“…Moreover, compared with traditional computational methods, the ML methods can provide cheap and highly accurate simulation processes. Paruzzo et al reported a ML workflow for simulating the results of chemical shifts in solids which are always gained by NMR. ML models are based on computational data from Cambridge Structural Database (CSD), and the models have acceptable accuracy even though no data of experimental shifts are used for the training step.…”
Section: Achievements Of ML In Energy Storage and Conversion Materialsmentioning
confidence: 99%